2020
DOI: 10.1302/0301-620x.102b2.bjj-2019-0420.r2
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric and adolescent anterior cruciate ligament reconstruction surgery

Abstract: Aims Anterior cruciate ligament (ACL) surgery in children and the adolescent population has increased steadily over recent years. We used a national database to look at trends in ACL reconstruction and rates of serious complications, growth disturbance, and revision surgery, over 20 years. Methods All hospital episodes for patients undergoing ACL reconstruction, under the age of 20 years, between 1 April 1997 and 31 March 2017, were extracted by procedure code from the national Hospital Episode Statistics (HES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…In fact, no patients underwent partial epiphysiodesis or realignment osteotomy, an occurrence which has been reported to reach more than 1%. 18 A similar concept of combined intra-articular and extra articular extra-osseous reconstruction has already been employed by Kocher et al 12 using iliotibial band in 237 skeletally immature Tanner 1 or 2 patients, reporting satisfactory outcomes in terms of failure rate (6.6%), subjective scores, and respect of skeletal growth. Both techniques are easy to perform and respectful of immature physis, but the latter allows for increase of the graft size respective to the iliotibial band, which is only minimally affected, reducing the tissue invasively.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In fact, no patients underwent partial epiphysiodesis or realignment osteotomy, an occurrence which has been reported to reach more than 1%. 18 A similar concept of combined intra-articular and extra articular extra-osseous reconstruction has already been employed by Kocher et al 12 using iliotibial band in 237 skeletally immature Tanner 1 or 2 patients, reporting satisfactory outcomes in terms of failure rate (6.6%), subjective scores, and respect of skeletal growth. Both techniques are easy to perform and respectful of immature physis, but the latter allows for increase of the graft size respective to the iliotibial band, which is only minimally affected, reducing the tissue invasively.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies from registries and national databases have demonstrated that the rate of anterior cruciate ligament (ACL) ruptures in children and adolescents has increased over the past decade. 18,19 A rapid growth of 15.7% in the 15- to 19-year-old cohort and of 27.6% in the 10- to 14-year-old cohort was in fact reported between 2007 and 2011, 29 and a 29-fold increase was estimated from 1997 to 2017. 18…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Per year, over two million ACL injuries occur worldwide. The majority of these injuries are observed in paediatric and adolescent athletes [6][7][8][9][10], with a higher incidence in girls compared to boys, especially at younger ages [11][12][13]. These ACL injuries lead to the longest withdrawal time from youth sports.…”
Section: Introductionmentioning
confidence: 99%
“…1,17,28 The incidence of ACL injuries in the pediatric and adolescent population has increased in recent years, due in part to the increase in youth competitive athletic activity with yearround training and competition. 14,20,24,28,39 An ACL rupture is a serious knee injury that may lead to an inability for young individuals to return to sports at their previous recreational or competitive level, despite receiving the best possible treatment. 11,23,38 A rupture of the ACL can lead to functional knee instability, with episodes of giving way when walking or during other everyday activities.…”
mentioning
confidence: 99%